Research on the service modeling method of information management software based on the petri net model - Rui, S.; Xiaoyan, W. (Journal of Digital Information Management, 2013)
With the continuous development of science and technology, the development of the enterprise also requires the agility of enterprises. At present,SOA is one of the most popular means of achieving enterprise's agility.This article embarks on the Petri net model to study the service modeling method of information management software. Firstly, it introduces service-oriented architecture SOA and the methodology of service modeling SOMA, it has been understood its theoretical basis.Secondly, it expounds the structure and characteristics of Petri net. And then it introduces the PN -SM modeling process and the basic structure of the model. Finally, it draws the conclusion: Petri net is a kind of system model that suitable for describing concurrent characteristic.
Keywords: Petri Net; PN-SM; SOA; SOMA

Semantic-oriented integration and simulation-based analysis approach for healthcare information systems (HIS) - Song, L.-L.; Xie, J.; Huang, Z.-D. (Journal of Digital Information Management, 2012)
According to the unsystematic state of current health information systems integration and aiming to improve semantic interoperability, the approach for health information systems under SOA is studied in detailed. As for the system engineering, the concept of HIS integration is discussed. After that, a SOA-based health information system architecture and MDA-based modeling and simulation analysis approach are explored. Finally, a service-oriented integrated environment is designed.
Keywords: Healthcare information system; MDA; Simulation analysis; SOA